La nouvelle police Assurance-incendie (110Q, 5-83), contrat en coassurance - Moreau, Rémi (Assurances, 1984)
At our request, Me Rémi Moreau looks at the Fire Subscription Policy, entitled in French Assurance-incendie, contrat en coassurance. He compares the new text with that which applied up to May 1983. He concludes that there appears to be no fundamental change, subject to the new general conditions required by the new Law on lnsurance. As to the format, the author believes that there is a real attempt at improvement, both in the layout and the terms used.